2018
DOI: 10.15416/ijcp.2018.7.2.99
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Antihypertensive Drug Use on Ischemic Stroke Patients at National Stroke Hospital Bukittinggi

Abstract: AbstrakObat antihipertensi menjadi salah satu obat yang paling banyak diresepkan pada pasien stroke iskemik. Penatalaksanaan hipertensi yang tidak tepat pada kedaruratan neurovaskular akut dapat meningkatkan risiko kerusakan otak dan saraf. Penggunaan obat antihipertensi harus dievaluasi melalui program evaluasi penggunaan obat (EPO) untuk menjamin penggunaan obat yang rasional. Penelitian ini bertujuan untuk mengkaji kerasionalan/ketepatan penggunaan obat antihipertensi pada pasien stroke iskemik meliputi tep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 8 publications
(14 reference statements)
0
0
0
Order By: Relevance
“…Another study also stated that 53.5% of the patients were male and had an age range of 45 to 65 years. 4 Several previous studies also indicate that strokes most commonly occur in individuals aged over 50 years. 4,5,6 Our research found that the percentage of essential drug (government formulary) utilization is not influenced by gender, age, or length of stay.…”
Section: Patient Characteristics Vs Essential Drug Utilizationmentioning
confidence: 95%
See 2 more Smart Citations
“…Another study also stated that 53.5% of the patients were male and had an age range of 45 to 65 years. 4 Several previous studies also indicate that strokes most commonly occur in individuals aged over 50 years. 4,5,6 Our research found that the percentage of essential drug (government formulary) utilization is not influenced by gender, age, or length of stay.…”
Section: Patient Characteristics Vs Essential Drug Utilizationmentioning
confidence: 95%
“…4 Several previous studies also indicate that strokes most commonly occur in individuals aged over 50 years. 4,5,6 Our research found that the percentage of essential drug (government formulary) utilization is not influenced by gender, age, or length of stay. There hasn't been any specific study yet that directly associates the percentage of essential drug (government formulary) utilization in stroke patients with patient characteristics.…”
Section: Patient Characteristics Vs Essential Drug Utilizationmentioning
confidence: 95%
See 1 more Smart Citation
“…Kata kunci: Antiplatelet, Aspirin, PTT aPTT, Stroke Berulang Lipoprotein (HDL) ( Juwita, et al, 2018).…”
Section: Abstrakmentioning
confidence: 99%
“…Hasil penelitian sebelumnya dari Dian dan Dedi tentang evaluasi penggunaan obat Antihipertensi pada pasien stroke iskemik di Bukit Tinggi hasil penelitian menunjukan ketepatan penggunaan obat antihipertensi yaitu 100% tepat indikasi, 84% tepat obat, 96% tepat dosis, 98% tepat frekuensi dan 100% tepat pasien. Ketidaktepatan yang di temui yaitu ketidaktepatan kombinasi obat (11).…”
Section: Pendahuluanunclassified